The Role of International Law in Addressing Immigration Barriers: a Study on the Indonesian Passport - Ikhwannul Kholis; Sofa Laela (Civiliza Publishing, 2026)
Cross-border mobility has become a central feature of global interaction, yet access to international travel remains highly unequal, as reflected in disparities in passport strength. In this context, the Indonesian passport continues to face significant immigration barriers, including visa restrictions, administrative requirements, and risk-based entry policies imposed by destination countries. This study aims to identify the types of immigration barriers affecting the Indonesian passport and to assess the extent to which international law can address these challenges. The research adopts a normative legal approach, supported by conceptual and comparative analysis, drawing on international legal instruments, bilateral and regional agreements, and global mobility data. The findings demonstrate that immigration barriers are shaped by the interaction of legal restrictions, political relations, and structural factors, including migration risk perceptions and economic disparities. While international law provides a normative framework through principles such as freedom of movement and non-discrimination, and facilitates cooperation through bilateral and regional mechanisms, its effectiveness remains limited in practice. This limitation is primarily due to the enduring dominance of state sovereignty, which allows states to regulate entry and mobility based on national interests without binding obligations to ensure equal access. The study concludes that international law functions as a facilitative rather than determinative instrument in addressing immigration barriers. Accordingly, strengthening the Indonesian passport requires a multidimensional strategy that integrates legal frameworks with diplomatic engagement, institutional capacity, and trust-building in the international system.